Pendampingan Metode Pembalajaran Kewirausahaan Dengan Sistem Bisnis Model Canvas Pada SMA Muhammadiyah 1 Malang - Iqbal Ramadhani Fuadiputra; Kardina Yudha Parwati; M. Fika Fitriasari (Jurnal Pengabdian Manajemen, 2022)
The community service program proposed by the devotees will be carried out at SMA Muhammadiyah 1 Malang. The process of situation analysis and identification of problems with service partners was carried out on March 3, 2021. Based on the situation analysis process, the service found that entrepreneurship subject activities at SMA Muhammadiyah 1 Malang still need to be readjusted related to business details that must be built when setting up a business. Because of this need, we as a servant answer this by providing assistance with entrepreneurship learning methods with the canvas business model method. The purpose of the implementation of this service program is to provide knowledge and improve the skills of teachers in creating new businesses which will later be applied in entrepreneurship subjects at SMA Muhammadiyah 1 Malang. In this service, the servant will provide assistance to teachers in using the Business Model Canvas method. Through this service program, it is hoped that entrepreneurship subject teachers can apply it during the teaching and learning process.